Transportation and trade interactions: A trade facilitation perspective - Jerónimo Carballo; Georg Schaur; Christian Volpe Martincus (Inter-American Development Bank (IDB), 2017)
Trade facilitation policies intend to simplify administrative processes and accelerate the handling of shipments across borders. Recent research shows that these policies have substantial effects on trade flows. In this chapter, we discuss what the existing evidence for trade implies for the provision of transportation services. In addition, we make use of a particular policy change, an upgrade to a new transit trade regime, to illustrate the many direct and indirect linkages between trade facilitation and transportation. These multiple connections imply that a well-functioning transportation sector is important to realize the full potential of trade facilitation policies. Our conceptual and empirical analyses show that, despite an increase in demand for transportation services, the effect of trade facilitation on freight rates and the underlying transportation sector is far from obvious. This calls for future research to examine equilibrium adjustment channels to trade facilitation policies in the transportation sector.
hdl:11319/8177
Keywords: F10; F13; F14; 330; Transportation; Trade Facilitation; Trade Costs; Trade Policy